2014
DOI: 10.1371/journal.pntd.0003364
|View full text |Cite
|
Sign up to set email alerts
|

Population Genetics of Two Key Mosquito Vectors of Rift Valley Fever Virus Reveals New Insights into the Changing Disease Outbreak Patterns in Kenya

Abstract: Rift Valley fever (RVF) outbreaks in Kenya have increased in frequency and range to include northeastern Kenya where viruses are increasingly being isolated from known (Aedes mcintoshi) and newly-associated (Ae. ochraceus) vectors. The factors contributing to these changing outbreak patterns are unclear and the population genetic structure of key vectors and/or specific virus-vector associations, in particular, are under-studied. By conducting mitochondrial and nuclear DNA analyses on >220 Kenyan specimens of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
35
0
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 32 publications
(36 citation statements)
references
References 58 publications
0
35
0
1
Order By: Relevance
“…tarsalis in the United States and the arrival of West Nile virus [66] and also with Ae . ochraceus , which acted as an important vector in the epidemic caused by Rift Valley fever virus in Kenya in 2007 [67]. …”
Section: Discussionmentioning
confidence: 99%
“…tarsalis in the United States and the arrival of West Nile virus [66] and also with Ae . ochraceus , which acted as an important vector in the epidemic caused by Rift Valley fever virus in Kenya in 2007 [67]. …”
Section: Discussionmentioning
confidence: 99%
“…In the LV basin, population genetic studies on the Anopheles gambiae Giles complex (Chen et al. 2004, 2006) reflects research concentration on malaria, while at LB, mitochondrial and nuclear gene studies on Aedes mcintoshi Huang highlight this vector’s importance in RVF virus transmission (Tchouassi et al. 2014).…”
mentioning
confidence: 99%
“…However, genetic analyses to support morphology provides better taxonomic elucidation of species diversity (Kumar et al. 2007), thereby unraveling insights into disease epidemiology driven by the population genetic structures of species and subspecies (Tchouassi et al. 2014).…”
mentioning
confidence: 99%
“…ochraceus sampled from various sites in north-eastern Kenya and West Africa affected by RVF outbreaks revealed that Ae . ochraceus constituted a recently introduced species to Kenya [22]. …”
Section: Discussionmentioning
confidence: 99%